Comparative study of lipid profile and C-reactive protein in hypertensive and normotensive patients of Andhra Pradesh population - Shaikh, Yasar Arafath (International Journal of Advances in Medicine, 2019)
Background: Parameters of lipid profile, C-reactive protein was studied in hypertensive and Normotensive adults aged between 25 to 60 years and compared to predict the cardio-vascular disease. Methods: BP was recorded in both groups and compared. CRP lipid profile was studied in both groups and compared. Results: Systolic BP, diastolic BP in HTN and Normotensive were compared statically and p value was highly significant (p <0.01). C-reactive protein of both HTN and Normotensive was compared and statically highly significant (p <0.01). The lipid profile parameters total cholesterol, triglyceride VLDL, HDL, LDL were also compared in both HTN and Normotensive and all values were statistically highly significant (p <0.01). Conclusion: This study highlighted the diagnostic and prognostic values of HTN and cardiovascular diseases, which have high rates of morbidity and mortality.